2006
DOI: 10.1590/s1516-44462006000200009
|View full text |Cite
|
Sign up to set email alerts
|

Teenage pregnancy: use of drugs in the third trimester and prevalence of psychiatric disorders

Abstract: A b s t r a c t Objective: To determine the prevalence of psychiatric disorders during pregnancy, the prevalence of cocaine and marijuana use during the third trimester of gestation and the socio-demographic characteristics of a population of low-income teenagers. Method: One thousand pregnant teenagers were evaluated using the Composite International Diagnostic Interview, and a sociodemographic and socio-economic questionnaire at the obstetric center of a public hospital in São Paulo, Brazil. Hair sample was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1
16

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 12 publications
(4 reference statements)
1
23
1
16
Order By: Relevance
“…The following risk factors were associated with increased odds of antenatal depression: (1) having a casual job (i.e., occasional employment doing low-paying work); (2) history of a previous self-reported depression or of any prior psychiatric treatment; (3) an unplanned pregnancy; and (4) several recent (past-year) stressful life events (loss of a confidant, serious physical illness and financial difficulties). The prevalence of major depression during pregnancy (14.2%) was not remarkably different from most previous reports based on studies conducted in Brazil 4,7,13,14,26,29,37 . In these studies the antenatal major depressive disorder prevalence ranged from 13% to 20.8%.…”
Section: Discussion Prevalence Of Depression During Pregnancy and Riscontrasting
confidence: 79%
See 2 more Smart Citations
“…The following risk factors were associated with increased odds of antenatal depression: (1) having a casual job (i.e., occasional employment doing low-paying work); (2) history of a previous self-reported depression or of any prior psychiatric treatment; (3) an unplanned pregnancy; and (4) several recent (past-year) stressful life events (loss of a confidant, serious physical illness and financial difficulties). The prevalence of major depression during pregnancy (14.2%) was not remarkably different from most previous reports based on studies conducted in Brazil 4,7,13,14,26,29,37 . In these studies the antenatal major depressive disorder prevalence ranged from 13% to 20.8%.…”
Section: Discussion Prevalence Of Depression During Pregnancy and Riscontrasting
confidence: 79%
“…a study that reported an antenatal depression prevalence of 37.9%) reported prevalence rates ranging from 13% to 20.8% 4,7,12,14,26,29,37 . The validity of these findings still needs to be established as the majority of these studies focused on pregnant adolescents 4,26,29,37 and women receiving prenatal care in obstetric out-patient clinics in hospital settings 7,12,14,26,29 . These samples are likely to be biased because women with high-risk pregnancies are more likely to seek prenatal care in hospitals.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, it constitutes a tool for critical awareness of people. A study has shown that the educational process results in behavior change when the reciprocal group dialogue and the life experience of communities are taken into consideration (18) .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that factors such as dysfunctional families, truancy, unemployment and low professional training contribute to the maintenance of an unfavorable socioeconomic situation and to the high prevalence of cocaine and marijuana use by pregnant adolescents and those with psychiatric disorders (18,19) . Another study that corroborates these results found that the use of chemical substances, such as marijuana and alcohol, is correlated with the phenomenon of adolescent pregnancy because in many cases experience with drugs precedes adolescent pregnancy.…”
Section: Adolescent Drug Addition and Pregnancymentioning
confidence: 99%